2015
DOI: 10.1080/10447318.2015.1070553
|View full text |Cite
|
Sign up to set email alerts
|

A Weighted QFD-Based Usability Evaluation Method for Elderly in Smart Cars

Abstract: The aim of this research is to develop a quantitative usability evaluation method (UEM) for elderly drivers, which has different weight values on each factor concerning physical and cognitive context of elderly drivers. An analysis of the relationship between universal design guidelines for elderly drivers and usability principles was conducted by using the quality function deployment method. In addition, developmental priorities are derived from analysis results of difficulty in achieving performance improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…And some scholars put forward the user-centered design method for the design of smart clothing for the elderly and suggested that the user's evaluation tendency of smart clothing should be involved in the design process [ 10 ]. Some scholars used Quality Function Development (QFD) to study the relationship between universal design criteria and usability principles to establish a usability evaluation method for intelligent elderly vehicles [ 11 ]. To reduce the subjectivity of choosing the design scheme of intelligent elderly accompanying products, some scholars put forward an evaluation method of the design scheme of healthy elderly accompanying products [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…And some scholars put forward the user-centered design method for the design of smart clothing for the elderly and suggested that the user's evaluation tendency of smart clothing should be involved in the design process [ 10 ]. Some scholars used Quality Function Development (QFD) to study the relationship between universal design criteria and usability principles to establish a usability evaluation method for intelligent elderly vehicles [ 11 ]. To reduce the subjectivity of choosing the design scheme of intelligent elderly accompanying products, some scholars put forward an evaluation method of the design scheme of healthy elderly accompanying products [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many authors have implemented the QFD in their studies addressing the design of products and services with particular focus on customer experience and alternative ways to capture user's feedback as in the works by Iranmanesh et al, Choi et al, Vezzetti et al, Violante et al, Sun et al [35][36][37][38][39]. The reputation of the QFD as a reference framework for design and quality management can be attributable to the multiple advantages it offers.…”
Section: The Quality Function Deploymentmentioning
confidence: 99%